2019
DOI: 10.1021/acs.energyfuels.9b00408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Asphaltenes Precipitation: Direct and Indirect Analyses and Phase Equilibrium Study

Abstract: Asphaltenes precipitation is still a challenge for the petroleum industry during crude oil production and processing. Pressure, composition, and temperature variation can induce asphaltenes destabilization and aggregation, leading to fouling and flow blocking in pipelines and wellbore pores. The present work aims to investigate the effect of temperature on asphaltene precipitation using n-heptane as the precipitant alkane. Three different Brazilian crude oils, here named BR1, BR2, and BR3, were studied at temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, the growth of particle sizes decreased after reaching its peak MED of 11.54 μm for the first 300 min in the 70 °C model oil system. The sharp decrease in the particle size was probably due to the enhancement of asphaltene solubility upon increasing temperature . In contrast, the particle sizes of the 50 °C model oil system maintained a consistent buildup for 2880 min reaching an MED of 13.39 μm.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…However, the growth of particle sizes decreased after reaching its peak MED of 11.54 μm for the first 300 min in the 70 °C model oil system. The sharp decrease in the particle size was probably due to the enhancement of asphaltene solubility upon increasing temperature . In contrast, the particle sizes of the 50 °C model oil system maintained a consistent buildup for 2880 min reaching an MED of 13.39 μm.…”
Section: Resultsmentioning
confidence: 91%
“…The sharp decrease in the particle size was probably due to the enhancement of asphaltene solubility upon increasing temperature. 17 In contrast, the particle sizes of the 50 °C model oil However, after 2880 min, a sharp decline in the MED from 2880 to 7200 min was noticed. The confocal experimentation confirmed the accumulated yield experiments, which implied that asphaltene precipitation yielded more regarding decreasing temperature.…”
Section: Effects Of Temperature On Particle Size-time Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several thermodynamic models including cubic equations of state, the cubic plus association equation of state, statistical associating fluid theory, and regular solution theory have been applied to asphaltene precipitation from heavy oils diluted with pure n -alkanes. , Reviews of the performance of thermodynamic models with pure solvents can be found elsewhere. , In this study, only the regular solution approach is considered because it was specifically designed to model asphaltene precipitation from mixtures of heavy oil and solvents.…”
Section: Introductionmentioning
confidence: 99%